Метод определения структуры и содержания учебного материала, формирующего проектную культуру будущих инженеров-педагогов в процессе системотехнической подготовки - Ашеров, Акива Товиевич; Шеховцова, В. И. (НТУ "ХПИ", 2009)
In the article is expounded the method, which allow stodevelop such changes in the teaching material of disciplines of systems engineering cycle that enable to move from forming of complex of project's skills to forming of the designed culture of future engineers - pedagogues and masters of skills training in the computer industry.
Keywords: инженерно-педагогические специальности; специальности компьютерного профиля; инженеры-преподаватели; дисциплины компьютерные; дисциплины системотехнические; системно-аналитические умения